Os direitos linguísticos : possibilidades de tratamento da realidade plurilíngue nacional a partir da Constituição da República Federativa do Brasil de 1988 - Abreu, Ricardo Nascimento (2016)
The modern notion of language rights leads at least to the confluence of three landmark that have come to mark out the relationship of nation states and their language: a historical landmark, which refers to the drafting of the Universal Declaration of Human Rights in 1948, which emerged linguistic rights to a human rights category and fostered the positivization of a significant number of these rights in the constitutions of various countries; a legal landmark, which, in Brazil coincides with the enactment of the Constitution of the Republic, in 1988 and the strengthening among us, of a vision centered on fundamental rights, a theoretical landmark, which although strongly interdisciplinary, is mostly populated by the development of researches on language policy, sociology of language and also in the sociolinguistics field, which have instrumented researches that has generated meaningful data about the linguistic diversity of national states, defined methodological safe criteria, besides presenting language categories from which, countries can guide the development of their legislation. Another hallmark of this scenario is the fact that states usually legislate about the linguistic rights starting from two complementary normative biases, but distinct: in a first bias, the languages law, taking their own languages as legal objects to be protected by the States and, in a second bias, the linguistic rights of individual and groups, who understands to be the object of state protects the fundamental right of individuals and groups to use their own languages and / or the official language of the state in social situations formality or informality. This study aims to analyze the Brazilian state plurilingual situation under the bias and on the possibilities of the Federal Constitution of 1988, trying to extract a reading that can enable the guarantee language rights to individuals and groups speakers of minority languages, as well as understanding how Brazil appropriates the languages spoken in its territory, establishing a relationship between the official language and other languages constitutive of its linguistic diversity.